Optimization of process conditions for lactic acid recovery using organic base - Jamal, Parveen; Mel, Maizirwan; Abdul Karim, Mohamed Ismail; Syahida, N. (Springer-Verlag Berlin Heidelberg, 2008)
Lactic acid has a wide range of applications in food, pharmaceutical and cosmetics industries. The global market for lactic acid in foods is estimated at 275,000 tons with average annual growth of 10 per cent. The persistent demand of pure and naturally produced lactic acid in food and beverage applications attracted researcher’s interest towards process development for maximum recovery of lactic acid from fermentation broth. In this study, an organic base with appropriate diluent was used and optimization of process conditions was done by using central composite design from Statistica software to determine the optimum conditions for recovery of lactic acid. The effects of initial lactic acid concentration, pH, stirring rate, the amount of triisooctylamine in decanol, the ratio of organic phase volume to aqueous phase volume Vorg/Vaq, on the distribution coefficients of the lactic acid, KD,and the percentage extraction of lactic acid were investigated. The optimum process conditions showed maximum recovery of 94.47%, (w/w) and KD value was 17.12.